Patterns of gene recombination shape var gene repertoires in Plasmodium falciparum: comparisons of geographically diverse isolates - Levin Emily; Wang Wendy; Smith Leia M; Christodoulou Zoe; Nelson Siri O; Springer Amy L; Aggarwal Gautam; Kyes Sue A; Kraemer Susan M; Newbold Christopher I; Myler Peter J; Smith Joseph D (BMC Genomics, 2007)
Abstract Background Var genes encode a family of virulence factors known as PfEMP1 (Plasmodium falciparum erythrocyte membrane protein 1) which are responsible for both antigenic variation and cytoadherence of infected erythrocytes. Although these molecules play a central role in malaria pathogenesis, the mechanisms generating variant antigen diversification are poorly understood. To investigate var gene evolution, we compared the variant antigen repertoires from three geographically diverse parasite isolates: the 3D7 genome reference isolate; the recently sequenced HB3 isolate; and the IT4/25/5 (IT4) parasite isolate which retains the capacity to cytoadhere in vitro and in vivo. Results These comparisons revealed that only two var genes (var1csa and var2csa) are conserved in all three isolates and one var gene (Type 3 var) has homologs in IT4 and 3D7. While the remaining 50 plus genes in each isolate are highly divergent most can be classified into the three previously defined major groups (A, B, and C) on the basis of 5' flanking sequence and chromosome location. Repertoire-wide sequence comparisons suggest that the conserved homologs are evolving separately from other var genes and that genes in group A have diverged from other groups. Conclusion These findings support the existence of a var gene recombination hierarchy that restricts recombination possibilities and has a central role in the functional and immunological adaptation of var genes.